The bad neighbour - Iancu Sasul (1579–1582) - Milewski, Dariusz (Balcanica Posnaniensia. Acta et studia, 2025)
The paper discusses the issue of the “black legend” of the Moldavian hospodar Ioan (Iancu) Sasul in Polish historiography. It is so well-established that the hospodar is even considered a typical example of a bad neighbour. The analysis of his reign reveals both real and exaggerat ed reasons for accusing the hospodar of hostility towards Poland. Motives of his actions and the circumstances, in which the accusations of bad neighbourhood emerged were presented by reviewing information about the hospodar in available archival materials and source editions. It was indicated that there is a lack of primary information independently confirming the allegations that arose within the circle of King Stefan Batory and Chancellor Jan Zamoyski. At the same time, an objective conflict of interest between the king and the hospodar is indicated. Thus, the possibility of creating a bad image of the hospodar as a political justification for his brutal elimination on the orders of the Polish king is discussed.